Service-Learning and Chinese College Students' Knowledge Transfer Development - Wang, Cong; Yan, Wenfan; Guo, Fangfang; Li, Yulan; Yao, Meilin (Frontiers in Psychology, 2020)
As a form of experiential education, service-learning (SL) shows great potential for promoting students’ knowledge transfer as it offers students opportunities to apply what they have learned in classrooms to serve communities in real-life contexts. To explore how students’ knowledge transfer evolves during SL, we collected longitudinal survey data from 96 Chinese college students in a 9-week SL program. Results indicate that (a) students’ perceived knowledge transfer in SL did not follow a linear trajectory. Although students’ perceived knowledge transfer at the end of SL was significantly higher than those at the beginning, a slight drop was observed in the middle of SL; (b) the developmental pattern of perceived knowledge transfer varied across students; and (c) students’ perceived knowledge transfer development during SL was associated with mastery goal orientation and perceptions of psychologically controlling behaviors from their SL supervisors. By providing evidence of the dynamic process and mechanisms of students’ knowledge transfer development, the present study adds to our understanding of how, when, and why the benefits of SL are realized.